SIRT6 Activator UBCS039 Inhibits Thioacetamide-Induced Hepatic Injury In Vitro and In Vivo - Jiao, Fangzhou; Zhang, Zongwei; Hu, Hongtu; Zhang, Yongxi; Xiong, Yong (Frontiers in Pharmacology, 2022)
SIRT6 has been reported multiple function involved in inflammation and metabolism. In present study, we explored the regulatory effects and mechanisms of SIRT6 in thioacetamide (TAA)-induced mice acute liver failure (ALF) models. SIRT6 activator UBCS039 was administered in this animal experiment and cell experiments. We observed that UBCS039 ameliorated the liver damage, including inflammatory responses and oxidative stress. Further study of mechanisms showed that upregulation of SIRT6 inhibited inflammation reaction by suppressing Nuclear factor-κB (NF-κB) pathway in TAA-mediated ALF mice model and lipopolysaccharide (LPS) -stimulated macrophages. In addition, upregulation of SIRT6 alleviated the oxidative stress damage in hepatocytes by regulating Nrf2/HO-1 pathway. These findings demonstrate that pharmacologic activator of SIRT6 could be a promising target for ALF.